(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
A company indeed depends on its research anddevelopmental activities in order to have a niche over its competitors.Complete knowledge of the factors that have an effect on the innovationstrategy of a company is essential for the success of the research anddevelopment programmes of the company. Various internal and external factorsgreatly influence a business’ success. While it is practically impossible tocontrol forces outside the business, like world economic conditions and capitalavailability, management must guide and inspire internal operations to ensure acompetitive position in the marketplace. Adaptability and innovation arecrucial to gaining market share and staying profitable in fluctuating economicclimates. This research is something about that explains how a Nike shoe brandwill make itself strong enough to face the challenges in the businessenvironment in which it is operating .It has to make full utilization of itsstrengths , avail all the opportunities , make serious efforts to overcome itsweakness and faces the threats with full vigor.